Pengembangan Media Pembelajaran Berbasis Augmented Reality Book Simulasi Perkembangbiakan Hewan Pada Mata Pelajaran IPA Studi Kasus Kelas VI- SD Negeri 4 Suwug - Sudarmayana, I Gede Arya; Kesiman, Made Windu Antara; Sugihartini, Nyoman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2021)
The purpose of this research is to develop learning media based on the Augmented Reality Book of Animal Breeding on the Android platform, as one of the media to facilitate and provide it’s an attraction in understanding animal breeding material in Natural Sciences (IPA) lessons in SDN 4 SUWUG. The development of the Augmented Reality Book Animal Breeding application uses the ADDIE model which consists of five stages, namely the Analyze, Design, Development, Implementation, and Evaluation stages. In this model, an Evaluation process is carried out in each of the stages that are passed continuously to produce products that meet the needs in the field. The final result of this development is in the form of Augmented Reality Animal Breeding applications that can be used via mobile devices with the Android operating system. The final results of this study indicate that the application of Augmented Reality Animal Breeding is included in the criteria very well. The results obtained based on the black-box test obtained a percentage of success of 100%, white-box test obtained a percentage of success of 100%, content expert test, and media expert test were processed with Gregory Technique with an average of 1.00 calculation results if converted into a table of achievement levels expert validity criteria included Very High, and for the user response test with a percentage of 93.4% so that it falls into the rating criteria that is Very Good.